2008
DOI: 10.1089/lap.2008.0155
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response Is No Different in Children Randomized to Laparoscopic or Open Appendectomy

Abstract: We found no differences in inflammatory parameters after open and laparoscopic appendectomy for nonperforated appendicitis. However, surgeons send their laparoscopically operated patients home earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Differences in several inflammatory parameters after these two procedures were detected. 5,26 In particular, Li et al reported that the increase (pre-vs. postoperative) in IL-6 levels in the open group was markedly higher than that laparoscopic group. 5 Following laparoscopy in an experimental model, higher immune performance of peritoneal macrophages and pro-duction of the inflammatory mediator nitric oxide was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in several inflammatory parameters after these two procedures were detected. 5,26 In particular, Li et al reported that the increase (pre-vs. postoperative) in IL-6 levels in the open group was markedly higher than that laparoscopic group. 5 Following laparoscopy in an experimental model, higher immune performance of peritoneal macrophages and pro-duction of the inflammatory mediator nitric oxide was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Simon et al . [24] found that inflammatory markers such as body temperature, leukocyte count, hematocrit and serum levels of C-reactive protein (CRP), IL-6, TNF, sTNF-R, IL-1ra, sIL-2r and IL-8 were no different in children undergoing laparoscopic or open appendectomy (QoE-C3). An assessment of surgical stress using CRP and leukocyte count did not reveal any difference between children undergoing laparoscopy-assisted and posterior sagittal anorectoplasty for imperforate anus (QoE-C4).…”
Section: Discussionmentioning
confidence: 99%
“…Todavia, em outros artigos esse parâmetro não cursou com diferença significativa entre eles, sendo ambos afetados de forma semelhante (ALI R et al 2018;LITTLE DC et al 2002). Já outros ensaios clínicos observaram a ausência dessa infecção independente da abordagem cirúrgica realizada (LAVONIUS MI et al 2001;SIMON P et al 2009).…”
Section: Complicações Pós-operatóriasunclassified
“…3.2 TEMPO DE INTERNAÇÃOO tempo de internação após cirurgia variou entre os artigos analisados. Foi encontrado um tempo de internação significativamente menor (p<0,01) na AL em comparação com a AA em três estudos(ALI R et al 2018;SIMON P et al 2009;LINTULA H et al 2001). O menor tempo de internação na AL se dá provavelmente pelo fato de serem feitas menores incisões associada a menores níveis de dor pós-operatória e uma mobilização mais precoce(ALI R et al 2018).…”
unclassified